Comparative analysis of the strength to compression, flexure and workability of traditional concrete versus a concrete using steel slag as fine aggregate (Gaceta Técnica, 2022)
The objective of this research is to determine the influence of slag as a global aggregate on compressive strength, bending and workability for a concrete f'c=20594 kPa. Steel slag was used in 10%, 15% and 20% as fine aggregate, in this way an alternative for the use of recycled materials is shown, in order to create an efficient and economical concrete, as well as friendly with the environment, where there is a large amount of steel slag, coming from workshops and companies dedicated to metal structures. This is due to the fact that they use steel welding, in order to minimize environmental contamination, since it would be shown that the steel slag would have a good behavior for the development of an experimental concrete. The method used is quantitative, using data observation panels as a data collection tool, they use inferential statistics of the data obtained to demonstrate hypotheses. It was concluded that the breakage, wear and elasticity tests carried out at 7, 14 and 28 days provided the optimal design to use 10% for the use of recycled steel slag in the three pre-established objectives
Keywords: steel slag; compressive strength; bending and workability